Seasonality in the condition and variability in somatic relationships of megrim (Lepidorhombus whiffiagonis) in the northeast Atlantic - Landa, Jorge; Korta, M.; Iriondo, A.; Fontenla-Giráldez, Jorge; Gancedo, Rosa María; Reparaz, María; Rodríguez-Fernández, Lorena; Loureiro-Caride, María Isabel; Gómez-González, Antonio; Castro-Loehmann, Begoña; Antolínez, Ana; Bruno, Isabel; et al. (Estuarine, Coastal and Shelf Science, 2022)
Somatic parameters’ estimation of megrim (Lepidorhombus whiffiagonis), an economically important flatfish species and relevant one in the benthic community, is essential in fisheries biology. It helps us to deepen our understanding of the species life history traits and an adequate stock assessment and fishery management. Le Cren’s condition factor (K), weight-length relationships and weight conversion factors were studied in megrim for more than two decades time-series (1998–2019) and wide area with a relevant fishing activity and the species is distributed into two stocks: northern Bay of Biscay-nBB and Celtic Sea-CS stock, and southern Bay of BiscaysBB and Galician waters-Gw stock. Around 30,000 specimens, mostly collected from commercial landings by the research institutions IEO and AZTI, were sampled. Total fish length, total weight and commercial gutted weight were obtained, and five-year periods were defined throughout in the time-series. The influence of several factors, as seasonality, temporality, fish sex, maturity, abundance, and environmental conditions on the megrim condition were analyzed for each stock by GLM, being the season the most relevant factor. A clear seasonal pattern found for K, with the lowest values in spring, was found in both populations for the first time based on a multiyear period analysis. The pattern was more prominent in females and less marked in immature, related to the reproduction process. The lowest condition value was observed in May in nBB-CS and a month earlier in sBB-Gw (both after the spawning period). A progressive increase (favorable feeding conditions) followed to highest values in November–February, showing the relevance of K as indicator of the nutritional/reproductive status of megrim. Temporality (five-year periods) also had a much smaller effect on condition than seasonality. Megrim condition was inversely related to its abundance, and to the NAO index in the nBB-CS stock. Total weight-length, gutted weight-length and total weight-gutted weight relationships ...